2004
DOI: 10.1016/j.bbrc.2004.07.060
|View full text |Cite
|
Sign up to set email alerts
|

Highly infectious SARS-CoV pseudotyped virus reveals the cell tropism and its correlation with receptor expression

Abstract: Studies of SARS coronavirus (SARS-CoV)-the causative agent of severe acute respiratory syndrome (SARS)-have been hampered by its high transmission rate and the pathogenicity of this virus. To permit analysis of the host range and entry mechanism of SARS-CoV, we incorporated the humanized SARS-CoV spike (S) glycoprotein into HIV particles to generate a highly infectious SARS-CoV pseudotyped virus. The infection on Vero E6-a permissive cell line to SARS-CoV-could be neutralized by sera from convalescent SARS pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
119
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(126 citation statements)
references
References 27 publications
(31 reference statements)
7
119
0
Order By: Relevance
“…It has been shown that SARS-CoV uses ACE-II (angiotensinconverting enzyme 2) as the cellular receptor [18,19]. A good correlation between the expression of ACE-II and tissue tropism has been shown [20]; however, the presence of ACE-II is unlikely to be the sole determinant for tropism [21]. The C-type lectin CD209L (L-SIGN) human cellular glycoprotein may also possibly be a receptor for SARS-CoV [22].…”
Section: The Virusmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been shown that SARS-CoV uses ACE-II (angiotensinconverting enzyme 2) as the cellular receptor [18,19]. A good correlation between the expression of ACE-II and tissue tropism has been shown [20]; however, the presence of ACE-II is unlikely to be the sole determinant for tropism [21]. The C-type lectin CD209L (L-SIGN) human cellular glycoprotein may also possibly be a receptor for SARS-CoV [22].…”
Section: The Virusmentioning
confidence: 96%
“…Haematological disturbances have been suspected to be a result of both direct viral and immune-mediated mechanisms affecting haematopoiesis [16]. The S protein may be the main factor in determining the severity of clinical disease, because of its roles in viral entry, pathogenesis, antiviral response, virulence and cellular and species tropism [8,20,45,79]. Again, studies on animal coronavirus S proteins have helped to define this.…”
Section: Pathogenesismentioning
confidence: 97%
“…Thus, Huh-7 and 293T cells are permissive to both NL63-and SARS-CoV-S-driven infection (13,16,18) and express the SARS-CoV receptor ACE2 (20,(23)(24)(25), whereas CEMx174, HeLa, and HOS cells are not permissive (13,16,18) and do not express ACE2 (20,25). We therefore determined whether ACE2 plays a role in HCoV-NL63 infection.…”
Section: Hcov-nl63 Engages Ace2 As a Receptor For Infectious Cellularmentioning
confidence: 99%
“…because of the high level of GFP expression in the VSVDG* system (Ogino et al, 2003). In contrast, the time required for infection in the pseudotype retrovirus system is 48 h (Moore et al, 2004;Nie et al, 2004), which is similar to the time required for SARS-CoV to replicate to a level that results in plaque-forming or cytopathic effects in infected cells. To date, there have been no reports of VSV pseudotyped with the S protein of a coronavirus.…”
mentioning
confidence: 95%
“…The SARS-CoV-S protein has a 13 aa signal peptide at its N terminus, a single ectodomain of 1182 aa and a transmembrane region followed by a cytoplasmic domain of 28 aa (Marra et al, 2003;Rota et al, 2003). Recently, pseudotyped retroviruses bearing SARS-CoV-S protein have been generated by several laboratories (Hofmann et al, 2004;Nie et al, 2004;Simmons et al, 2004). It has been shown that these pseudotyped viruses have a cell tropism identical to SARS-CoV and that their infection is dependent on a receptor molecule, angiotensin-converting enzyme 2 (ACE2), indicating that infection is mediated solely by SARS-CoV-S protein.…”
mentioning
confidence: 99%